2011
DOI: 10.1192/apt.bp.109.007310
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute agitation in psychosis: an evidence-based approach in the USA

Abstract: SummaryAgitation in psychiatric settings, particularly in psychosis, presents a staggering challenge for clinicians, who must both manage the patient's acute symptoms and simultaneously make an accurate diagnosis. Too often, the management of the former confounds the latter. Patients are very often sedated medically, which masks their underlying condition, rendering accurate diagnosis delayed and inherently difficult. Significant data are available regarding both pharmacological and non-pharmacological interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
12

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 54 publications
0
25
1
12
Order By: Relevance
“…When de-escalation techniques are ineffective, patients experiencing acute agitation and loss of self-control may need rapid tranquilization to decrease dangerous behavior and allow treatment of the underlying psychiatric condition (Schleifer, 2011). Hospital nurses need to coordinate care effectively with physicians to identify and recommend needed medications.…”
Section: Psychotropicsmentioning
confidence: 99%
“…When de-escalation techniques are ineffective, patients experiencing acute agitation and loss of self-control may need rapid tranquilization to decrease dangerous behavior and allow treatment of the underlying psychiatric condition (Schleifer, 2011). Hospital nurses need to coordinate care effectively with physicians to identify and recommend needed medications.…”
Section: Psychotropicsmentioning
confidence: 99%
“…The main limitations of antipsychotic use in rapid tranquillisation include sedation, route of administration, speed of onset and adverse effect profile. Patients are very often sedated medically, rendering the accurate diagnosis delayed and inherently difficult (Schleifer 2011). The goal for rapid tranquillisation of the agitated patient is to allow for a reduction in agitation or aggression without sedation, allowing the service user to participate in further assessment or treatment (NICE 2002;Allen 2005).…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…Although agitation states from mild to severe and their characterization have been previously described, there has been a failure to reach a consensus on the definition of agitation [ 6 , 7 ] which has been recognised as one factor underlying the lack of epidemiological data in this area [ 8 ]. Previous studies that have reported on the prevalence of agitation focus on emergency hospital or clinic attendance; a European study found that 4.6% of psychiatric emergencies were attributed to acute agitation, of which half of the patients had a diagnosis of schizophrenia and a quarter had a diagnosis of bipolar disorder [ 9 ].…”
Section: Introductionmentioning
confidence: 99%